2018
DOI: 10.1037/npe0000091
|View full text |Cite
|
Sign up to set email alerts
|

Social purpose increases direct-to-borrower microfinance investments by reducing physiologic arousal.

Abstract: Websites offering microfinance loans have become an increasingly popular form of investment. However, it is unclear why some projects offered on sites such as Kiva.org, Microplace.com, and Lendforpeace.org are more successful at meeting funding goals than others. The present article reports the results of an experiment to test if communicating social purpose enhances investment appeal and the neurophysiological mechanism through which this effect occurs. By connecting physiological and behavioral responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Organizations with understood and lived Purposes have higher retention and are more profitable ( Harter et al, 2002 ; Deloitte., 2014 ). Research from our group has shown that tasks with Purpose reduce physiologic arousal, consistent with the actions of OT ( Kraig et al, 2018 ). We therefore hypothesized that, along with Trust, an understanding of the organization’s Purpose is another physiologic route through which colleagues induce OT release in each other.…”
Section: Theorymentioning
confidence: 60%
“…Organizations with understood and lived Purposes have higher retention and are more profitable ( Harter et al, 2002 ; Deloitte., 2014 ). Research from our group has shown that tasks with Purpose reduce physiologic arousal, consistent with the actions of OT ( Kraig et al, 2018 ). We therefore hypothesized that, along with Trust, an understanding of the organization’s Purpose is another physiologic route through which colleagues induce OT release in each other.…”
Section: Theorymentioning
confidence: 60%
“…Linking neurophysiologic responses to an observable post-stimulus behavior increases the likelihood that captured neural responses are signal and not noise (Cacioppo et al, 2000 ). For example, participants can be offered an opportunity to respond to a video or text stimulus by donating to a charity, investing in an African entrepreneur, or purchasing a product (Kraig et al, 2018 , 2019 ; Falk and Scholz, 2018 ; Morris et al, 2019 ). While many studies of video influences on behavior have relied on self-reported engagement (Yu et al, 2018 ; Wohn and Freeman, 2020 ), this induces an endogeneity problem: participants who spend more time watching will report more engagement in the stimulus.…”
Section: Introductionmentioning
confidence: 99%